Регуляторы роста растений: применение в сельском хозяйстве / Л. Дж. Никелл - Никелл Л. Дж. (Колос, 1984)
Экземпляры: КХ (20060425) / Инвентарный номер: 828408 / Сис.шифр: 41.2 / Авт.знак: Н 62 / ГРНТИ: 68 / ББК: 41.27